Disorders in Gianyar Bali Mask Making Craftsman - Pemayun, Cokorda Gde Putra; Saputra, I Kadek Dwi; Irwanti, Ni Ketut Dewi; Dharmayanti, Cokorda Istri Putri (CV. Global Health Science Group, 2024)
In the process of making masks, many occupational health problems are found, such as workers working in a sitting posture with their bodies bent and their legs bent while sitting on an uneven surface and working for quite a long time, which will have an impact on the emergence of health problems such as the emergence of complaints. musculoskeletal disorders. This study aims to analyze the relationship between the incidence of complaints of musculoskeletal disorders in mask making craftsmen. The method used in this research uses a quantitative research design with a cross-sectional analytical approach, the sampling technique in this research uses a total sampling technique from all 17 workers, the data collected is primary data and univariate analysis and analysis tests are carried out. bivariate with Chi-square test to look for relationships. The results of the research found that 64.7% of respondents experienced complaints of musculoskeletal disorders (MSDs) and based on the results of the chi-square test it was found that complaints of musculoskeletal disorders (MSDs) were significantly higher in age groupat age ≥30, work period ≥ 10 years, length of work, medium and heavy workload, risky work attitude and lighting levels that do not meet the requirements.